KADAR FORMALIN PADA IKAN ASIN JAMBAL ROTI (Arius thalassinus) DI KAWASAN WISATA TELUK PENYU CILACAP TAHUN 2014 - Seti Yuliowati; Febri Apwanti; Suparmin Suparmin (Poltekkes Kemenkes Semarang, 2015)
Background and objectives, Fish was an export commodity that decays faster than fruits andvegetables. Jambal roti fish is salted fish products derived from Manyung fish (Arius thalassinus), is oneof the food ingredients commonly mixed with food additive that forbidden by the government, namelyformalin. The purpose of the study was to determine the formaldehyde levels content in jambal roti (Ariusthalassinus) salted fish sold in Teluk Penyu tourist resort Cilacap 2014.The research design used was descriptive research with lab analyst, to obtain vivid descriptionrelated Jambal roti salted fish (Arius thalassinus)physical condition, measuring the traders knowledgelevel and formaldehyde levels examination jambal roti (Arius thalassinus) salted fish sold in Teluk Penyutourist resort Cilacap 2014.The research results shows from 10 samples the Jambal roti salted fish (Arius thalassinus) physicalcondition measured with organoleptic obtained good categories with 70% percentage. The examinationresults shows that from 10 samples, 9 samples proved negative (did not contain formaldehyde) on thenumber of samples 1,2,3,4,5,7,8,9,10 and 1 sample contained 0.5 mg of formaldehyde which is samplenumber 6.The conclusions drawn was the tested samples number 6 positive containing formaldehyde 0.5 mg,so that sample number 6 declared not safe for public consumption. The trader knowledge level relatedforbidden food additive was poor, researchers need to provide discourse related formaldehyde danger ifused as food additive in the future so that the trader knows about the dangers of formaldehyde was aforbidden food additive.